PROS AND CONS OF MOVING THE INDONESIAN CAPITAL CITY - Audrey Bintania Mahesa; Anantha Sukma Pratiwi; Carmen Eva Desire Sumampouw; Ester Cornelia Simanjuntak; Rena Anastasya (President University, 2021)
This journal analyzes the pros and cons of transferring the Capital City of Indonesia to the new Indonesian capital city (IKN) based on Law No.3 of 2022. On the positive side, the transfer Capital City assessed can push equality development, creating a new field and reducing the population burden on Java Island. However, there are also significant challenges and concerns. High costs, environmental impact, and questions about priority development become frequently debated points. This uses a qualitative study method to study literature and analyze documents. Secondary data was obtained from various sources, including government publications, report research, and news articles. Research also emphasizes the importance of transparency and accountability in the transfer process. Capital City ensures the use of efficient and effective power. This study recommends that transfer to the Capital City be done carefully, considering all the pros and cons and ensuring that all parties are interested in this process.Keywords: Transfer capital city; Capital city archipelago (IKN); Invite number 3 in 2022; Pros and Cons transfer capital city; Impact transfer capital city; Moving strategy capital city.